GFF Guidance Note: Inclusive Multi-stakeholder Country Platforms in Support of Every Woman Every Child - Global Financing Facility (Global Financing Facility, 2018)
The aims of this paper are: 1) to highlight how multi-stakeholder country platforms, built on development effectiveness principles, in line with the globally agreed recommendations of IHP+2, can be reinforced within the framework of the Global Strategy and its supporting mechanisms and are key to the Global Strategy’s successful implementation; and 2) to lay out key considerations for new multi-stakeholder country platforms, along with the relevant mechanisms and a minimum set of standards to support the process of national coordination among actors engaged in RMNCAH. This guidance note is intended to serve as a resource for countries committed to implementing the Global Strategy. This includes the 62 high-burden, low- and lower-middle income countries that are eligible to receive resources from the GFF Trust Fund. It will build on lessons from countries that have already developed or are currently developing prioritized RMNCAH Strategies or Investment Cases (IC)4 aligned with their broader national health plans and planning cycles and processes, for purposes of mobilizing resources, including from the GFF Trust Fund and other sources of funding. The GFF, H6 and PMNCH seek to bring together a broad set of partners and leverage their unique roles, comparative advantages and value added to maximize impact for improved outcomes for women, children and adolescents.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; gender / género; health / saúde; youth / juventude

Representation and Inclusion in School Councils in Mozambique - Taela, Kátia; López Franco, Erika; Alex, Shankland; Maivasse, Catija; Chilengue, Nárcya; Goodfry, Claudino (Institute of Development Studies, 2018)
This study was conducted as part of the Citizen Engagement Programme (Programa Cidadania e Participação (CEP)) in Mozambique – an empowerment and social accountability initiative to improve the quality of education and health services by increasing citizens’ influence on the management of schools and health units, the formulation of education and health policies, and the provision of education and health services. In education, CEP enabled citizen monitoring of services through the community scorecard (Cartão de Pontuação Comunitária (CPC)), focusing on the link between CPC action plans and the work plans of the co-management mechanism in schools – the school councils. CEP has also promoted the channelling of issues beyond the capacity and mandate of schools to higher levels of the national education system. This work identified a need to better understand the role of school councils as a link between the school and the community, and also in escalating important matters to higher levels of management in the education system, beyond that of school authorities. It was in this context that the Institute of Development Studies and the Centre for Learning and Capacity Building for Civil Society, both members of the CEP consortium, proposed to undertake a qualitative study on representation and inclusion in school councils. The primary aim of this study was to widen the knowledge base available to civil society and to government on the factors that contribute to good performance by school councils in building inclusivity and social accountability to improve the quality of education services.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; Important; L - english / inglês; M - ethnography / etnografia; access to services / acesso a serviços; citizenship & participation / cidadania e participação; civil society / sociedade civil; decentralization / descentralização; education / educação; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Comunicado: Conferência “Como está Moçambique?” - Instituto de Estudos Sociais e Económicos (IESE) (Instituto de Estudos Sociais e Económicos (IESE), 2018)
Veja e aceda ao comunicado subscrito pelas organizações da sociedade civil – Observatório do Meio Rural (OMR), Centro de Integridade Pública (CIP), Mecanismo de Apoio à Sociedade Civil (MASC) e Instituto de Estudos Sociais e Económicos (IESE), resultante da conferência “Como está Moçambique?”, que decorreu no dia 16 de Maio último, no Hotel Montebelo Indy, em Maputo. Leia o comunicado aqui.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil

Youth initiatives: Supporting citizen engagement with government and civic life - Orrnert, Anna (GSDRC, University of Birmingham, 2018)
There is a large volume of literature on youth participation in development, including on the benefits of involving young people in local, national, regional and global governance initiatives. Although not as voluminous, there is also a significant body of work on youth participation in civic life, though much of this focuses on issues of education and employment (Oxfam 2016) as well as health (particularly initiatives related to HIV/ AIDS). It was not possible to identify a large body of literature around more multi-faceted and holistic initiatives (for example, involving different themes and connecting at different levels).
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; citizenship & participation / cidadania e participação; civil society / sociedade civil; youth / juventude

Afrobarometer Round 7. Summary of Results for Mozambique, 2018 - Ipsos Mozambique (Ipsos Mozambiqu, 2018)
Afrobarometer is a pan-African, non-partisan research network that conducts public attitude surveys on democracy, governance, economic conditions, and related issues in countries across Africa. Six rounds of surveys were conducted between 1999 and 2015, and Round 7 surveys are being carried out in 2016-2018. Afrobarometer conducts face-toface interviews in the language of the respondent’s choice with nationally representative samples of 1,200 or 2,400 respondents. Afrobarometer is produced collaboratively by social scientists from across Africa. Coordination is provided by the Center for Democratic Development (CDD) in Ghana, the Institute for Justice and Reconciliation (IJR) in South Africa, the Institute for Development Studies (IDS) at the University of Nairobi in Kenya, and the Institute for Empirical Research in Political Economy/School of African Economics (IERPE/ASE) in Benin. Michigan State University (MSU) and the University of Cape Town (UCT) provide technical support to the network.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - survey / inquérito; civil society / sociedade civil; governance / governação